The effect of hosting 3.4 million refugees on the health system in Turkey and infant, child, and elderly mortality among natives - Aysun Aygün; Murat G. Kirdar; Berna Tuncay (Koç University-TÜSIAD Economic Research Forum (ERF), 2020)
As of the end of 2017, 3.4 million Syrian refugees lived in Turkey. These refugees left a country where the health system was completely broken. Several studies report that Syrian refugees faced numerous diseases during their exodus, brought certain infectious diseases to the hosting communities, and have a high incidence of health care utilization. Moreover, they have much higher fertility rates than natives (5.3 to 2.3). We examine the effect of Syrian refugees on the health infrastructure in Turkey and on natives' mortality - with a focus on infant, child, and elderly mortality. Our OLS results yield suggestive evidence of a negative effect of the refugee shock on infant and child mortality. However, we find that this is a result of endogenous settlement patterns of refugees. Once we account for the endogeneity using a plausibly exogenous instrument, we find no evidence of an effect on native mortality for any age group. We also analyze the pressure that the refugees put on the health care services in Turkey, as well as the government's response, to understand our findings on mortality outcomes.
Keywords: H51; I18; J13; J15; O15; 330; refugees; health care infrastructure; native mortality; infant; child; elderly; instrumental variables